PELATIHAN DAN PENDAMPINGAN EVALUASI BERBASIS HOTS UNTUK GURU BAHASA INDONESIA TINGKAT SMP SWASTA SEKOTA PALANGKA RAYA - Linggua Sanjaya Usop; Indra Perdana; Paul Diman; Lazarus Linarto (Bajang Institute, 2022)
The training and evaluation assistance based on Higher Order Thinking Skills (HOTS) is motivated by the teacher's pedagogic competence in developing the evaluation of learning outcomes that are still conventional. Therefore, community service that is carried out is based on the aim of increasing the ability of teachers to make questions that can encourage students to have the ability to analyze (C4), evaluate (C5), and create (C6). The program is Training on Preparation of High Order Thinking Skills (HOTS) for Indonesian Language Teachers in Palangka Raya City. This PKM activity is carried out by providing training and assistance in preparing lesson plans and making questions based on the guidelines for writing HOTS questions. Through lecture and practical methods, this training was able to open up the knowledge and understanding of teachers about the preparation of HOTS-based lesson plans, as well as improve the ability and skills of teachers in making questions at the level of higher-order thinking skills. So, that it can be used to measure the development of students thinking and reasoning correctly following the expected final learning outcomes, the whole community service activity can be successful. However, not all of the mentoring participants have mastered how to prepare HOTS questions.